Co-occurrence and ranking of entities based on semantic annotation. (12th November 2008) - Popov, Borislav; Kiryakov, Atanas; Kitchukov, Ilian; Angelov, Krasimir; , Danail Kozhuharov
This paper presents an extension of the KIM semantic annotation and search platform called CORE: Co-Occurrence and Ranking of Entities. It enables popularity timeline analysis and a novel faceted search interface. The idea and its advantages to the traditional keyword search are explained along with the environment, technical description and use case scenarios. The essence of the approach is a specific indexing, performed on the basis of semantic annotation of text with respect to named entities and key-phrases forming a reduced-dimension feature space. This allows for a sort of semantic search through adaptation of standard probabilistic IR models where documents are also considered contexts.